Haptics-mediated virtual embodiment: Impact of a wearable avatar-controlling system with kinesthetic gloves on embodiment in VR - Li, Zhenxing; Bujić, Mila; Buruk, Oğuz ‘Oz’; Bampouni, Elpida; Järvelä, Simo; Hamari, Juho (Frontiers in Virtual Reality, 2024)
Enhancing the experience of virtual reality (VR) through haptic feedback could benefit applications from leisure to rehabilitation and training. Devices which provide more realistic kinesthetic (force) feedback appear to hold more promise than their simpler vibrotactile counterparts. However, our understanding of kinesthetic feedback on virtual embodiment is still limited due to the novelty of appropriate kinesthetic devices. To contribute to the line of this research, we constructed a wearable system with state-of-the-art kinesthetic gloves for avatar full-body control, and conducted a between-subjects study involving an avatar self-touch task. We found that providing a kinesthetic sense of touch substantially strengthened the embodiment illusion in VR. We further explored the ability of these kinesthetic gloves to present virtual objects haptically. The gloves were found to provide useful haptic cues about the basic 3D structure and stiffness of objects for a discrimination task. This is one of the first studies to explore virtual embodiment by employing state-of-the-art kinesthetic gloves in full-body VR.